The association of intimate Partner violence and decision making power on nutritional status of married women in Ethiopia: a multilevel mixed-effect analysis - Fentanesh Nibret Tiruneh; Peter Austin Morton Ntenda; Tinebeb Tamir (BMC, 2023)
Abstract Background A growing body of research has established a link between intimate partner violence (IPV) and decision-making autonomy on women's mental, physical, and reproductive health consequences, as well as child nutritional status. However, there is a scarcity of research on the effects of IPV and decision-making autonomy on women's nutritional status. To date, no research has been conducted in Ethiopia to investigate the impact of IPV and decision-making autonomy on women's nutritional status. Therefore, the purpose of this study was to investigate the relationship between IPV and decision-making power at both the individual and community levels on women's nutritional status. Methods We analyzed data from the 2016 Ethiopian demographic and health survey. Our study focused on 3,660 married non-pregnant women of reproductive age. We used the chi-squared test and spearman correlation coefficients for bivariate analysis. The relationship between IPV and decision making power with nutritional status was evaluated using multilevel binary logistic regression models while controlling other determinants. Results Around 28% of women reported at least one of the four types of IPV. Approximately 32% of women had no decision-making power at home. About 27.1% of women were underweight (BMI < 18.5), while 10.6% were overweight/obese (BMI ≥ 25). Women who had sexual IPV had a higher chance of being underweight (AOR = 2.97; 95% CI: 2.02-4.38) than women who had no sexual IPV. While women who had decision-making power at home were at lower odds of being underweight (AOR = 0.83; 95% CI: 0.69-0.98) than their counterparts. The findings also revealed a negative relationship between being overweight/obese and community-level women's decision-making autonomy (AOR = 0.75; 95% CI 0.34-0.89). Conclusions Our findings show the presence of a significant association between IPV & decision-making autonomy with women's nutritional status. Therefore, effective policies and programs to end violence against women and encourage women to participate in decision-making are required. This will help to improve the nutritional status of women as well as the nutritional outcomes of their families. This study suggests that efforts to achieve Sustainable Development Goal (SDG5) may have an impact on other SDGs particularly SDG2.